2000
DOI: 10.1117/12.384447
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the ratio difference of overlapped areas of stereoscopic images on each eye in a teleoperation

Abstract: It is reported that the efficiency of a teleoperation in stereoscopic images of the working site is lower than that in the direct viewing of the site. It is assumed that one of the causes of lower efficiency of the teleoperation in the stereoscopic images would be the difficulty ofthe fusion of images, which would be caused by the imperfect overlapping ofimages on each eye. Through most of a teleoperation the convergence of the stereoscopic cameras is fixed at a certain point, usually in the middle of the work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The visual system of the observer had to make up or ignore the deficits. Our previous simulation experiment showed that the low overlap rate brought low performance in pick-and-insert task as we anticipated 3) . In this paper we did an experiment using the actual stereoscopic video system.…”
Section: Introductionmentioning
confidence: 79%
“…The visual system of the observer had to make up or ignore the deficits. Our previous simulation experiment showed that the low overlap rate brought low performance in pick-and-insert task as we anticipated 3) . In this paper we did an experiment using the actual stereoscopic video system.…”
Section: Introductionmentioning
confidence: 79%
“…in the personal space, at arm's length) and during procedures that demands for high dexterity as a surgical tasks. It is our conviction that this requirement, once achieved, may fully compensate for the increased distortion of the perceived 3D space, due to the dynamic change of the convergence of the cameras (be them virtual or real) [37]. In our opinion, from a functional standpoint, resolving diplopia has a higher priority than dealing with the perceptual artefacts caused to the non-rigorous orthoscopy of the stereoscopic display.…”
Section: Discussionmentioning
confidence: 96%
“…To cope with this, both hardware and software solutions have been proposed [30]. As an example of a hardware solution, the excessive retinal disparity can be overcome by physically converging the cameras [31], [32] so as to increase the overlapping zones between the left and right images and thus yielding a correct stereoscopic vision even of the closest objects without diplopia. However, as previously mentioned, the optical axes of cameras and displays need to be coincident to prevent geometric and stereoscopic distortions, such as keystone distortion and depth plane curvature.…”
Section: Related Workmentioning
confidence: 99%